how do you find it and the steps to solve it -7=-2(x-1)
1
Expert's answer
2014-06-02T04:21:32-0400
Reverse the equality in -7=-2(x-1) in order to isolate x to the left hand side.
-7=-2(x-1) is equivalent to -2(x-1)=-7.
Divide both sides a constant to simplify the equation. Divide both sides of -2(x-1)=-7 by -2. Any nonzero number divided by itself is one. -2/(-2)=1: x-1=-7/(-2).
Simplify the sign of -7/(-2). The sign of -7/(-2) is positive, so -7/(-2)=7/2.
x-1=7/2.
Isolate terms with x to the left hand side. Add 1 to both sides: x+(1-1)=7/2+1.
Look for two terms that sum to zero. 1-1=0: x=7/2+1.
Comments
Leave a comment